1982
DOI: 10.1080/00268948208074474
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Angular Dependence of NMR Relaxation Times in Macroscopically Oriented Lyotropic Liquid Crystal Lamellar Phases

Abstract: The angular dependence of 'H and *H NMR relaxation rates has been investigated for macroscopically oriented multi-bilayers of egg yolk lecithin and dimytistoyl lecithin in the La phase. Proton TI, values show a strong dependence on the orientation of the bilayer normals to the magnetic field, while deuterium TI, and TI values and proton TI'S show little or no orientation dependence. The results are interpreted on the basis of a simple modification of the theory of Ukleja, Pirs and Doane for relaxation in orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…A number of nuclear magnetic resonance (NMR) investigations have focused on the molecular motions of phospholipids in a pure lipid bilayer, and various theoretical models have been proposed (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Aside from those studies emphasizing lateral diffusion (9,19), most existing models of the dynamics of phospholipids belong to one of two classes: (i) one or more noncollective anisotropic rotations of a lipid molecule (or a segment of the molecule) with well-defined correlation times (6-8, 10, 11, 16-18, 22); or (ii) collective bilayer disturbances with small angular modulations and a broad distribution of correlation times (13)(14)(15)20).…”
mentioning
confidence: 99%
“…A number of nuclear magnetic resonance (NMR) investigations have focused on the molecular motions of phospholipids in a pure lipid bilayer, and various theoretical models have been proposed (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Aside from those studies emphasizing lateral diffusion (9,19), most existing models of the dynamics of phospholipids belong to one of two classes: (i) one or more noncollective anisotropic rotations of a lipid molecule (or a segment of the molecule) with well-defined correlation times (6-8, 10, 11, 16-18, 22); or (ii) collective bilayer disturbances with small angular modulations and a broad distribution of correlation times (13)(14)(15)20).…”
mentioning
confidence: 99%
“…It is quite likely that this term exhibits a different orientation dependence compared with the relaxation caused by the local modulation of the orientation of a particular CF2 group. The second reason can also be used to explain the lack of agreement between the orientation dependence of oriented 2-[7,7-'9F2]DMPC-d52 bilayers and the orientation dependence of 'H Tp' reported by Pope et al (1982). In their case, the relaxation originates from the dipolar interactions among all the protons in the molecule.…”
Section: Differences Between Protonated and Perdeuterated Lipidsmentioning
confidence: 95%
“…This is also true in the case of the rotating-frame relaxation rate (T -') versus the locking field (HI) for multilamellar liposomes (Fisher and James, 1978). Secondly, the locking-field dependence of the proton rotating-frame spin-lattice relaxation rate of oriented lipid bilayers (Cornell and Pope, 1980;Pope et al, 1982) has been found to be well fitted by the conventional Lorentzian relaxation model with a single correlation time, and, combined with the orientation dependence of the relaxation rate, these data have been interpreted in terms of relaxation through a modulation of intermolecular interactions (Pope et al, 1982).…”
Section: Introductionmentioning
confidence: 91%
“…The slow molecular motions of phospholipids have been investigated by NMR using line-shape analysis (Campbell et al, 1979;Huang et al, 1980), spin-lattice relaxation either in low to medium magnetic fields or in the rotating frame (Fisher and James, 1978;Cornell and Pope, 1980;Pope et al, 1982;Kimmich et al, 1983;Brown et al, 1983 and1986), and spin-spin relaxation (Bloom and Sternin, 1987). Previous relaxation studies of slow motions have led to a few controversial conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation